The The Effect Of Academic Supervision, Work Experience, Skills And Managerial Work Commitment In The Principal Elementary School State In Batam Riau Islands - Sarmini (IJHCM (International Journal of Human Capital Management), 2021)
This study aims to investigate the influence of the academic supervision, work experience, and a commitment to work towards the managerial skills of school principals. This study uses a quantitative approach using a survey method. Path analysis was used to analyze the data collected. The population in this study are all heads of public primary schools in the city of Batam totaling 143 principals. The number of samples taken in this study were 106 randomly selected people. The results showed that the managerial skills of school principals directly influenced by the academic supervision, work experience, and job commitment. The study also found that the work commitment is influenced by the academic supervision and work experience. Based on these findings it can be concluded that any changes occur in the principal managerial skills are influenced by the academic supervision, work experience, and job commitment. Therefore, the managerial skills of principals, academic supervision, work experience, and job commitment can be taken into consideration in strategic planning for the development of human resources in the education sector.